2020
DOI: 10.1007/s00380-020-01659-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutritional index on long-term outcomes of elderly patients with coronary artery disease: sub-analysis of the SHINANO 5 year registry

Abstract: Nutritional status is a novel approach to prognostic assessment in patients with cardiovascular disease. However, assessment of nutritional status in elderly patients is challenging due to the significant differences between young patients. The TCBI (Triglycerides × Total cholesterol × Body Weight Index) is a novel and simple nutritional index for predicting long-term outcomes in patients with coronary artery disease. This retrospective study evaluated the efficacy of TCBI in 597 elderly (≥ 75 years) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Another recent study conducted to assess the magnitude of malnutrition in diabetic patients with CAD using the CONUT score demonstrated that 60.5% of patients with both CAD and diabetes suffered from malnutrition ( 37 ). Moreover, in concordant with our findings, malnutrition determined by the various malnutrition indices was significantly associated with adverse clinical outcomes in patients with CAD ( 11 , 38 40 ). Therefore, clinicians need to integrate malnutrition detection into their daily practice.…”
Section: Discussionsupporting
confidence: 91%
“…Another recent study conducted to assess the magnitude of malnutrition in diabetic patients with CAD using the CONUT score demonstrated that 60.5% of patients with both CAD and diabetes suffered from malnutrition ( 37 ). Moreover, in concordant with our findings, malnutrition determined by the various malnutrition indices was significantly associated with adverse clinical outcomes in patients with CAD ( 11 , 38 40 ). Therefore, clinicians need to integrate malnutrition detection into their daily practice.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, traditional risk scoring systems in patients with CCD may need to be modified to most accurately assess an older patient’s risk. 32,33 Older patients also have an increased prevalence of frailty, 34–37 malnourishment, 38–41 and cognitive decline, all of which may be associated with poor outcomes and treatment response. Equally important, older patients are more likely to prioritize the ability to remain independent, with a focus on maintaining their mobility and functional status rather than reducing their mortality rate.…”
Section: Special Populationsmentioning
confidence: 99%
“…Several nutritional scoring systems, including the prognostic nutritional index (PNI), CONUT, triglycerides-total cholesterol-body weight index (TCBI), Mini Nutritional Assessment (MSA), Graz Malnutrition Screening (GMS), and GNRI have been introduced for evaluating nutritional state in clinical practice. Malnutrition determined by the PNI ( 23 ), TCBI ( 24 , 25 ), and CONUT ( 3 ) was also significantly associated with adverse outcomes in patients with CAD ( 23 ). However, there is no consensus on which tools have the best predictive role in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Several nutritional scoring systems, including the prognostic nutritional index (PNI), CONUT, triglycerides-total cholesterolbody weight index (TCBI), Mini Nutritional Assessment (MSA), Graz Malnutrition Screening (GMS), and GNRI have been introduced for evaluating nutritional state in clinical practice. Malnutrition determined by the PNI (23), TCBI (24,25), FIGURE 4 | Forest plots showing the pooled RR and 95% CI of major adverse cardiovascular events for the lowest vs. the highest GNRI category. RR, risk ratio; CI, confidence interval; GNRI, Geriatric Nutritional Risk Index.…”
Section: Discussionmentioning
confidence: 99%